Analisis Sektor Basis dan Non Basis dalam Upaya Peningkatan Sarana dan Prasarana - Hendy Pramana Putra; Farida Rahmawati (EKONOMI & SOSIAL, 2022)
Regional economic development is one of the focuses in efforts to increase regional competitiveness. The government continues to increase the GRDP of Trenggalek Regency through the development of economic activities accompanied by increasing its supporting facilities. The purpose of this study was to determine the basic economic sector and the non-base economic sector in Trenggalek Regency. The research method used in this study is location quotient analysis (LQ, shift share analysis, and trendline analysis. The results of the Loqation Quotient (LQ) analysis explain that Trenggalek Regency has 8 non-base sectors. Meanwhile, the results of shift share analysis show that there are 6 sectors which is slightly backward or slow in growth. Then based on the polynomial trendline analysis, it is found that the population is predicted to increase in 2025 which is around 763,645 people, the increase is estimated to be dominated in the age category 20-35 years which is the projection of the workforce. This research is expected to be useful in determine the focus of improving the district's infrastructure or facilities and infrastructure, so that sectors that are included in the non-base category and sectors classified backward or with slow growth can be upgraded to basic and advanced sector classifications.